Dementia Caregiving Experiences and Health Across Geographic Contexts by Race and Ethnicity. (13th March 2023) - Kindratt, Tiffany B; Sylvers, Dominique L; Yoshikawa, Aya; López-Anuarbe, Mónika; Webster, Noah J; Bouldin, Erin D
Abstract: Objectives: Few studies have examined how the intersectionality of geographic context and race/ethnicity influences dementia caregiving. Our objectives were to determine whether caregiver experiences and health (a) differed across metro and nonmetro areas and (b) differed by caregiver race/ethnicity and geography. Methods: We used data from the 2017 National Health and Aging Trends Study and National Study of Caregiving. The sample included caregivers ( n = 808) of care recipients ages 65 and older with "probable" dementia ( n = 482). The geographic context was defined as the care recipient's residence in metro or nonmetro counties. Outcomes included caregiving experiences (care situation, burden, and gains) and health (self-rated anxiety, depression symptoms, and chronic health conditions). Results: Bivariate analyses indicated that nonmetro dementia caregivers were less racially/ethnically diverse (82.7% White, non-Hispanic) and more were spouses/partners (20.2%) than their metro counterparts (66.6% White, non-Hispanic; 13.3% spouses/partners). Among racial/ethnic minority dementia caregivers, nonmetro context was associated with more chronic conditions ( p < .01), providing less care ( p < .01), and not coresiding with care recipients ( p < .001). Multivariate analyses demonstrated that nonmetro minority dementia caregivers had 3.11 times higher odds (95% confidence interval [CI] = 1.11–9.00) of reporting anxiety in comparison to metro minority dementia caregivers. Discussion: Geographic context shapes dementia caregiving experiences and caregiver health differently across racial/ethnic groups. Findings are consistent with previous studies that have shown that feelings of uncertainty, helplessness, guilt, and distress are more prevalent among people providing caregiving from a distance. Despite higher rates of dementia and dementia-related mortality in nonmetro areas, findings suggest both positive and negative aspects of caregiving among White and racial/ethnic minority caregivers.